2011
DOI: 10.1186/1471-2334-11-189
|View full text |Cite
|
Sign up to set email alerts
|

Soil transmitted helminths and schistosoma mansoni infections among school children in zarima town, northwest Ethiopia

Abstract: BackgroundIn Ethiopia, because of low quality drinking water supply and latrine coverage, helminths infections are the second most predominant causes of outpatient morbidity. Indeed, there is a scarcity of information on the prevalence of soil transmitted helminths and Schistosomiasis in Ethiopia, special in study area. Therefore, the aim of this study was to determine the prevalence and associated risk factors of soil transmitted helminths and intestinal Schistosomiasis.MethodsCross-sectional study was conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

40
101
22
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(165 citation statements)
references
References 13 publications
40
101
22
2
Order By: Relevance
“…However, the combined use of both CRP and AGP can reduce underestimation of Fe deficiency prevalence essentially to zero (43) . Soil helminthes, gastrointestinal parasitic infestation, malaria (44,45) or indoor air pollution (46,47) could be some of the factors contributing to infection or inflammation in children from rural Ethiopia. In addition, 22·9 % of children in the present study reported illness during the two weeks preceding the survey.…”
Section: Discussionmentioning
confidence: 99%
“…However, the combined use of both CRP and AGP can reduce underestimation of Fe deficiency prevalence essentially to zero (43) . Soil helminthes, gastrointestinal parasitic infestation, malaria (44,45) or indoor air pollution (46,47) could be some of the factors contributing to infection or inflammation in children from rural Ethiopia. In addition, 22·9 % of children in the present study reported illness during the two weeks preceding the survey.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of infections varies according to socio-economical situations and hygienic behaviors [2,[4][5][6][7] . Contamination of water and food sources with human wastes and insufficient hygiene are main causes of fecal-oral transmitted intestinal parasitic infections [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…Soil-transmitted helminthes (STH) as a major health problem caused by Ascaris lumbricoides, Trichuris trichiura and the hookworms are the most prevalent worldwide [7] and, Strongyloides stercoralis (S. stercoralis) is the most neglected one among them [9,11,12] . It is estimated that over 1 billion people are infected with STH and 30-100 millions with S. stercoralis worldwide [7,[11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…La prevalencia en pueblos aborígenes de Malasia fl uctúa entre 4,6 a 86,7% 15 ; en Brasil diversos estudios demuestran prevalencias de 5,8 a 59,5% [16][17] . En Etiopía un estudio reciente demostró 22% de ascaridiasis 18 . Por otra parte, la frecuencia aumenta frente a situaciones de desastres naturales 19 .…”
Section: Discussionunclassified